Analisis daya dukung komoditas serealia terhadap ketahanan pangan Kabupaten Buleleng - Luh Pastiniasih (Bioculture Journal, 2023)
The increase in population has an impact on the reduction in the area of ​​productive agricultural land due to land conversion for various needs. This causes a decrease in food production so that food availability is lower and unbalanced with the demand or needs of the population. It is essential to know the carrying capacity of land as an illustration of a region's ability to meet its population's basic needs. This study aims to analyze the occurrence of conversion of agricultural land and its impact on the carrying capacity of land on food security in Buleleng Regency. The research is qualitative and descriptive, utilizing secondary data on agricultural land area, harvested area, production value, and population in ten years (2012-2021). The results showed that the carrying capacity of food fields in Buleleng Regency was low because they could not be self-sufficient or were in a deficit condition. This is due to the rapid population increase and agricultural land conversion, especially paddy fields. The authors thank the reviewers and the IASSF team for supporting this research.